2020
DOI: 10.1038/s41598-020-64963-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving root characterisation for genomic prediction in cassava

Abstract: Cassava is cultivated due to its drought tolerance and high carbohydrate-containing storage roots. The lack of uniformity and irregular shape of storage roots poses constraints on harvesting and postharvest processing. Here, we phenotyped the Genetic gain and offspring (C1) populations from the International Institute of Tropical Agriculture (IITA) breeding program using image analysis of storage root photographs taken in the field. In the genome-wide association analysis (GWAS), we detected for most shape and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
14
1
Order By: Relevance
“… Kengkanna et al (2019) developed cassava shovelomics to evaluate root architecture traits. More recently, Yonis et al (2020) , demonstrated the feasibility of root phenotyping using image capture and analysis. Routine implementation of these new phenotyping solutions offers new opportunities for cassava breeders to efficiently and precisely select and release cultivars with root architecture that are favorable for harvesting, processing, as well as selection for early bulking characteristics.…”
Section: Phenotyping Of Key Traitsmentioning
confidence: 99%
See 3 more Smart Citations
“… Kengkanna et al (2019) developed cassava shovelomics to evaluate root architecture traits. More recently, Yonis et al (2020) , demonstrated the feasibility of root phenotyping using image capture and analysis. Routine implementation of these new phenotyping solutions offers new opportunities for cassava breeders to efficiently and precisely select and release cultivars with root architecture that are favorable for harvesting, processing, as well as selection for early bulking characteristics.…”
Section: Phenotyping Of Key Traitsmentioning
confidence: 99%
“…There are great expectations for the use of GS in cassava breeding. Since the first GS studies in cassava conducted by de Oliveira et al (2012) and Ly et al (2013) , highlighting the potential of GS, several studies have been published ( Wolfe et al, 2017 ; Ozimati et al, 2018 ; de Andrade et al, 2019 ; Yonis et al, 2020 ). GS has been utilized in cassava breeding to increase resistance against CMD and CBSD in cassava populations ( Wolfe et al, 2016 ; Kayondo et al, 2018 ; Ozimati et al, 2018 ).…”
Section: Genomic Selection and It’s Potential In Cassava Breedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Cassava is one of the most important tropical staple foods, especially in Africa (http://faostat.fao.org). Among outbred, clonal crops, GS is relatively mature in cassava breeding (Yonis et al;de Oliveira et al 2012;Ly et al 2013;Wolfe et al 2016a;b, 2017;Okeke et al 2017;Elias et al 2018;Ozimati et al 2018) because of the Next Generation Cassava Breeding Project (http://www.nextgencassava.org, est. 2012), and the species can serve as a model for many others.…”
Section: Empirical Study Of Cassavamentioning
confidence: 99%